Dreamhunter - Knox, Elizabeth (New York : Square Fish, 2009)
In a world where select people can enter "The Place" and find dreams of every kind to share with others for a fee, a fifteen-year-old girl is training to be a dreamhunter when her father disappears, leaving her to carry on his mysterious mission.
School Library Journal
Wilson's Junior High School
Wilson's Senior High School
Young Adult.
Young Adult
Keywords: Dreams -- Juvenile fiction; Families -- Juvenile fiction; Dreams -- Fiction; Family life -- Fiction; Fantasy; Dreams -- Fiction; Family life -- Fiction; Fantastic fiction; Fantastic fiction